2006
DOI: 10.1507/endocrj.k06-032
|View full text |Cite
|
Sign up to set email alerts
|

Elevated Serum Bisphenol A Levels under Hyperandrogenic Conditions may be Caused by Decreased UDP-glucuronosyltransferase Activity

Abstract: Abstract. This study was performed to investigate the effect of androgen on the metabolism of bisphenol A (BPA), an endocrine disruptor, in order to clarify the mechanism of the higher levels of serum BPA in men and hyperandrogenemic women compared with normal women. Castrated female rats (OVX) were subcutaneously injected with testosterone propionate (TP) (0.01, 0.1, and 1 mg) every day for 2 weeks. Serum BPA concentrations in OVX rats showed a TP dosedependent increase and were significantly higher at 0.1 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
44
1
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(49 citation statements)
references
References 32 publications
2
44
1
2
Order By: Relevance
“…Two studies found women with polycystic ovarian syndrome (PCOS) had higher serum levels of BPA than did healthy control women (Takeuchi and Tsutsumi 2002;Takeuchi et al 2004). These studies also found a positive association between serum testosterone levels and BPA concentrations; this finding is especially interesting because it provides a potential basis for gender-biased exposures or metabolism of BPA (Takeuchi et al 2006).…”
Section: Healthymentioning
confidence: 72%
“…Two studies found women with polycystic ovarian syndrome (PCOS) had higher serum levels of BPA than did healthy control women (Takeuchi and Tsutsumi 2002;Takeuchi et al 2004). These studies also found a positive association between serum testosterone levels and BPA concentrations; this finding is especially interesting because it provides a potential basis for gender-biased exposures or metabolism of BPA (Takeuchi et al 2006).…”
Section: Healthymentioning
confidence: 72%
“…Also intriguing is the effect of BPA on one sex but not the other [45,46,48,58,66,[68][69][70][71][72][73]. The mechanisms responsible for different effects of BPA in males and females are not clear, although it is known that BPA metabolism is influenced by testosterone [74,75], and BPA modifies the metabolism of testosterone [41, 76,77]. Thus, one possibility is that the sex-specific effects of BPA in the brain and other tissues are due to an interaction with background levels of gonadal steroids.…”
Section: Behavioral Effectsmentioning
confidence: 99%
“…administration. [29][30][31] Corn oil has often been used as a solvent in administration of BPA, 10,22,32,33) and the bioavailability of hydrophobic compounds was improved by co-administration with oil. 34) The resulting level of BPA in the body in this study, in which deionized water was used basically as a matrix for administration, is thus considered to be lower than those in the experiments of other groups.…”
Section: Ova (µM)mentioning
confidence: 99%